Paham Teologi di Jawa Abad XVIII-XIX M.: Kajian atas Naskah Bayan at-Tasdiq - Syaifuddin Syaifuddin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2013)
This paper is a short discourse about a literature on theology in Java on 18th and 19th century, that is Bayan al-Tasdiq, one of many literatures on theology in Java. Having analyzed this book, this paper concludes that this book was fully used in the islamic boarding environment in Java at the time, even though the real author was unknown. it was proved that this book has been published in some versions with the same theme of discussion.Keywords: Teology, Bayan al-Tasdiq